City logistics: Towards a blockchain decision framework for collaborative parcel deliveries in micro-hubs. (November 2020) - Hribernik, Marko; Zero, Kathrin; Kummer, Sebastian; Herold, David M.
Highlights: Horizontal collaborations between CEPs in city logistics micro-hubs is problematic. Trust and data exchange are considerable barriers for cooperative parcel deliveries. Blockchain technology is presented as a possible solution for last-mile deliveries. We present a blockchain decision framework for collaborations between CEP carriers. Abstract: The growth in e-commerce has led to increased pressure within the courier, express and parcel (CEP) sector to tackle the 'last-mile' issue and come up with solutions that not only satisfy the customers, but also other stakeholders such as city councils and other regulatory bodies. Scholars have highlighted micro-hubs and the associated horizontal collaboration as a possible solution, which might help alleviate problems associated with last-mile logistics in inner-city centers. However, trust and data exchange issues are considerable barriers to the introduction of horizontal collaboration, in particular between CEP carriers. To address the lack of trust and the issue of data exchange between carriers, the use of blockchain technology may present a solution, but existing research so far is limited concerning frameworks that specifically discuss blockchain technology in the context of micro-hubs and last-mile deliveries. In response, this paper presents a blockchain decision framework for a horizontal collaboration between CEP carriers based on key characteristics of existing blockchain decision models and relevant related research in the area of logistics and last-mile distribution. This is the first study that specifically addresses the use of blockchain technology for horizontal collaboration in the context of micro-hubs and last-mile deliveries.